2013
DOI: 10.1002/cctc.201300212
|View full text |Cite
|
Sign up to set email alerts
|

CO Oxidation on Metal‐Supported Ultrathin Oxide Films: What Makes Them Active?

Abstract: It depends on O: The catalytic properties of ultrathin oxide films are studied by using the low‐temperature oxidation of CO as a benchmark reaction. The results reveal a strong correlation between the activity and the desorption energy of the most weakly bound oxygen species present on these films under net oxidizing conditions at near‐atmospheric pressures. The results suggest the use of oxygen binding energy as a suitable descriptor for the reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 76 publications
0
31
0
Order By: Relevance
“…By comparison with other films, we concluded that oxygen binding energy in the films plays the decisive role for the CO oxidation reaction in an excess of oxygen [11]. The more weakly bound the oxygen species, the higher the reaction rate.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…By comparison with other films, we concluded that oxygen binding energy in the films plays the decisive role for the CO oxidation reaction in an excess of oxygen [11]. The more weakly bound the oxygen species, the higher the reaction rate.…”
Section: Introductionmentioning
confidence: 83%
“…In contrast, the planar morphology of ZnO films grown on Ag(111) and Pt (111) is maintained in the reaction. For dense ZnO (0001) films, the CO oxidation rate is independent of the metal support, and this rate has turned out to be the smallest amongst the thin oxide films studied under the same conditions [11]. At submonolayer coverages, the ZnO/Pt (111) films used in these calculations were represented by a close-packed layer of metal cations (bonded to Pt) and a topmost layer of oxygen anions.…”
Section: Reactivity Of Metal-supported Zno(0001) Films: Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been observed to be the case in oxygen activation reactions such as 16 O 2 / 18 O 2 isotopic exchange [24] and oxidation of CH 4 [24], C 3 H 6 [25], H 2 [24][25][26][27] and CO [28][29][30]. The activity in the catalytic oxidation of CO on thin metal oxide films has also been correlated to the activation energy for oxygen desorption [31], which scales with the heat of chemisorption. Furthermore, the heat of chemisorption has also been found to be among the factors that play a role for the selectivity in oxidation of benzaldehyde [32] and methanol [33].…”
Section: Introductionmentioning
confidence: 99%
“…While several other oxide/metal combinations have meanwhile been tested for enhanced catalytic activity in CO oxidation [28], experimental verification of the promotional effect of a metal support in CO oxidation over ultra-thin MgO films is still lacking.…”
Section: Introductionmentioning
confidence: 99%